Linguistic Proficiency Assessment in Second Language Acquisition Research: The Elicited Imitation Task. Issue 2 (26th February 2016) - Gaillard, Stéphanie; Tremblay, Annie
Abstract : This study investigated the elicited imitation task (EIT) as a tool for measuring linguistic proficiency in a second/foreign (L2) language, focusing on French. Nonnative French speakers ( n = 94) and native French speakers ( n = 6) completed an EIT that included 50 sentences varying in length and complexity. Three raters evaluated productions on five scales: meaning, syntax, morphology, vocabulary, and pronunciation. Participants also completed a cloze test and a language background questionnaire. Results from regression and principal component analyses showed a strong relationship between EIT performance and cloze test scores and significant relationships between EIT performance, sentence length, and learners' knowledge of and experience with French. Ratings were internally consistent, and all test items discriminated well between lower‐ and higher‐level learners. We argue that this EIT exhibits good validity and reliability, discriminates among French learners of different proficiencies, and is a practical tool for L2 proficiency assessment.